INTERDISCIPLINARITY IN RESEARCH OF MODERN FAMILY - Jan Hlousek; Olga Sovova (European Scientific Journal, ESJ, 2015)
This article discusses the possibilities of using the knowledge of social anthropology for the development of social work. Social work often uses common terminology, approaches and research techniques together with other social sciences. Particular segment of social work as well as social anthropology focus on similar subjects - family, group, community. In these cases, social work can benefit from the research techniques of social anthropology. In our paper, we focus on the use of participatory visual methods to work with the family and the community. Participatory video is a set of techniques to involve a group or community in shaping and creating their own film on the topic of their own interest. It is the way of bringing people together to explore. It can be a highly effective tool to engage and mobilise marginalised people and to help them implement their own forms of sustainable development based on local needs. The article is one of results of particular research tasks in the project reg. CZ.1.07/2.3.00/20.0209 - Development and support of multidisciplinary scientific research team for the study of contemporary family UHK.